Creativity - Shalley, Christina E. (Henry Stewart Talks, 2012)
Definition of organizational creativity, Who is creative?, Characteristics of creative individuals, Creative personality factors, Three components of individual creativity, Conceptual blockbusters for creative thinking, Killer phrases, Be curious first...critical second, Provide leadership for creativity, Team creativity, Effective team brainstorming, Team characteristics for creativity
Reviewed at 2018/05/01